First Helicon Plasma Physics and Applications Workshop - Chang, Lei; Boswell, Rod; Luo, Guangnan (Frontiers in Physics, 2022)
The First Helicon Plasma Physics and Applications Workshop was held on 23-24 September 2021 through Zoom Cloud Meeting, instead of on-site gathering due to COVID-19 pandemic. It was convened by Rod Boswell (IOC) and Guangnan Luo (LOC), and organised by Lei Chang's group. The workshop attracted 110 registrations and 100 online audiences from 30 affiliations. There were 33 presentations covering the various fundamental physics of helicon plasma and its applications to space electric propulsion, material processing and magnetic confinement fusion. This paper highlights the presentations, discussions and perspectives given in the workshop, serving as reference for the helicon community.